Inteligência espiritual em um colégio confessional de Porto Alegre/RS - Silva, Maria dos Remédios Lima (2017)
The present research has as its main question understanding how Catholic confessional school in the city of Porto Alegre contributed to the development of the spiritual intelligence of the students who attended this institution from Elementary to High School with graduation from High School expected in 2016. The research was developed based on a qualitative, descriptive and interpretive methodological approach. The research method was initially phenomenological, following the hermeneutic-dialectical phenomenology. Three research documents of the school under study were used as research tools: Pedagogia Inaciana (PI - Ignatian Pedagogy), the Pedagogical Political Project (PPP) and the Commom Educational Project of the Jesuit Educational Network (PEC), as well as semi-structured interviews with students of high school in the studied institution. For analysis of the documents data, the analytical reading method was used according to Severino (2000); to analyze the interviews, we worked with TDA - Textual Discourse Analysis, according to Moraes and Galiazzi (2014). The understanding of the data implied a dialogical relationship among the collected data, the empirical data and the theoretical references, including the researcher's worldview in the interpretative process. In view of the whole research process, we arrived at the analysis of the research variables, which revealed three emergent categories: Values experience within the school space; Significant educational actions; Religion, Faith and Spirituality. Considering that all human beings have different intelligences, we will see some theories which affirm the existence of spiritual intelligence and its importance within a person’s life.